The effect of the order of reagent addition on the settling rate of aluminium hydroxide in the Al(III)-Na2CO3 system - Demirata, B; Apak, R; Gümüs, G; Afsar, H (KLUWER ACADEMIC PUBL, 2002)
The effects of several factors on the settling rate of aluminium hydroxide were investigated during chemical coagulation using aluminium salts. Experimental variables were pH, aluminium (III) concentration and the order of addition of reagents. Experiments were carried out at pH 5-8 and rapid settling was achieved when aluminium (III) solutions were added to Na2CO3 solutions near neutral pH, close to the minimum solubility pH of Al(OH)(3). For a narrow range of total Al concentration where Al(III) species were supersaturated with respect to the solid phase, Al(III)-added-to-carbonate type mixtures yielded a higher settling rate than mixtures obtained by the reverse order of reagent addition. The results were interpreted by comparing the rates of formation of polymer and solid (amorphous Al(OH)(3)) phases. It was concluded that Al(III) coagulants should be added to water containing natural or artificially incorporated carbonate alkalinity for rapid settling of Al(OH)(3) flocs.
Keywords: aluminium hydroxide precipitation; aluminium salts; coagulation; settling rate; sodium carbonate; X-RAY-SCATTERING; ENHANCED COAGULATION; PRECIPITATION; HYDROLYSIS; REMOVAL; ALUM; Environmental Sciences & Ecology; Meteorology & Atmospheric Sciences; Water Resources